Factors That Impact Fraud Prevention in Village Financial Management - Rahmawati, Wita; Nurhayati, Enung; Puspasari, Oktaviani Rita (Fakultas Ekonomi Universitas Garut, 2025)
In recent years, the government has annually allocated a large amount of funds to villages as a form of commitment to accelerate development and empowerment of rural communities. However, the large allocation of village funds is at risk of causing irregularities. The purpose this study was to determine the effect of religiosity, locus of control, transparency, bystander effect, and whistleblowing system on fraud prevention in village financial management. This study uses a quantitative method with a stratified random sampling technique. The respondent sample consisted of 105 people from three sub-districts in Cirebon Regency, namely Ciledug District, Pabuaran District, and Waled District. The units of analysis of this study were the village head, village secretary, finance officer, head of BPD (Village Consultative Body), and head of LPMD (Village Community Empowerment Institution) through direct distribution of questionnaires. This study uses the IBM SPSS version 22 data processing program. which uses multiple linear regression data analysis techniques. The results of the study indicate that religiosity, focus of control, transparency, and whistleblowing system have a positive and significant effect on fraud prevention in village financial management. While the bystander effect has a negative and significant effect on fraud prevention in village financial management.